1999
DOI: 10.1046/j.1420-9101.1999.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of evolution in Graomys griseoflavus (Rodentia, Muridae). IV. A case of rapid speciation

Abstract: The South American group of rodents known as Graomys griseoflavus comprises two sibling species differing only in diploid chromosomal complement: G. griseoflavus (2n = 36, 37 and 38) and G. centralis (2n=42). Reproductive barriers comprising postzygotic as well as precopulatory mechanisms prevent gene exchange between these species. We have studied genetic polymorphism in two populations of G. centralis and four of G. griseoflavus by means of gel electrophoresis of enzymes and other proteins giving information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 43 publications
(45 reference statements)
1
26
1
Order By: Relevance
“…Molecular‐cytogenetic analysis of chromosome evolution of Graomys griseoflavus showed a marked differentiation between 2n=42–41 and 2n=38–34 karyomorphic groups. Based on allozyme patterns and reproductive behavior T heiler (1996b) and T heiler et al (1999) revised the taxonomic status of Graomys species and reassigned them to: Graomys centralis , for 2n=42 specimens, and Graomys griseoflavus , for those of the 2n=38–36 complex, although the author did not include in the revision 2n=41, 35 and 34 individuals. The genetic differentiation observed with nuclear and non‐nuclear DNA markers, supports the observation that 2n=42–41 and 2n=38–34 constitute two (or even more) sibling species.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular‐cytogenetic analysis of chromosome evolution of Graomys griseoflavus showed a marked differentiation between 2n=42–41 and 2n=38–34 karyomorphic groups. Based on allozyme patterns and reproductive behavior T heiler (1996b) and T heiler et al (1999) revised the taxonomic status of Graomys species and reassigned them to: Graomys centralis , for 2n=42 specimens, and Graomys griseoflavus , for those of the 2n=38–36 complex, although the author did not include in the revision 2n=41, 35 and 34 individuals. The genetic differentiation observed with nuclear and non‐nuclear DNA markers, supports the observation that 2n=42–41 and 2n=38–34 constitute two (or even more) sibling species.…”
Section: Final Remarksmentioning
confidence: 99%
“…In spite D‐loop region is a highly evolving sequence, phylogenetic trees did not exhibited a clear differentiation among 2n=38–34 animals, indicating that Rb animals could constitute a genetically homogeneous group (unpublished). T heiler et al (1999) proposed that fixation of RF15‐17, 16‐18, and 1‐6 in the 2n=38–36 group has occurred without a bottleneck effect. Opposed to T heiler ′s proposal, the concordance between nuclear and mitochondrial DNA data supports the single origin hypothesis for Graomys Rb races; therefore, the occurrence of a founder effect during chromosomal differentiation cannot be rule out.…”
Section: Final Remarksmentioning
confidence: 99%
“…Compared to polyploid cytotypes there are far fewer examples of cytotypes with chromosome number polymorphisms caused by dysploidy. Examples are Graomys griseoflavus (2n = 36-38; Cricetidae) (Theiler et al 1999) and Crocus pallasii subsp. pallasii (2n = 14 and 16; Iridaceae) (Karamplianis et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The cytotypes 2n ¼ 36, 37, and 38 are karyotypically mixed populations and occur mainly in the Monte Desert and Patagonic steppe, whereas cytotype 2n ¼ 42 occurs in the Espinal and in Western Chaco ecoregions (Theiler et al 1999).…”
mentioning
confidence: 99%
“…Phylogenetic studies based on Cyt b and D-loop fragments of the mtDNA showed that animals with 2n ¼ 41 and 2n ¼ 42 form a separate clade from individuals with 2n ¼ 34-38, the latter being included in another well-supported group (Catanesi et al 2002 (Theiler 1997;Tiranti 1998;Theiler et al 1999) described 2n ¼ 42 cytotypes in individuals found in localities near Cruz del Eje, the site where the type specimens of Graomys centralis Thomas (1902) was obtained.…”
mentioning
confidence: 99%